Wokół wartości i zasad konstytucyjnych - Kropiwnicki, Robert (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The article covers discussions connected with principles of law as well as constitutional principles and values. All these notions underpin a legal system, their role is particularly important when it comes to conflicts related to the application of constitutional norms. Outlining a catalogue of constitutional values is helpful in settling the most significant matters, which may arise from the different understanding of the constitution. Principles of law are a broader notion than constitutional principles. This work describes various ways of understanding principles of law though the author defines them according to the concept by Robert Alexy and which are understood as optimisation commands. The final part of the article focuses on relations between constitutional values and constitutional principles. The author decides that principles transpose values into law, their catalogues do not exclude each other and can compliment one another.
Keywords: constitutional principles; constitutional values; principles of law